2008
DOI: 10.1002/ar.20644
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Evidence for Interconnections Between the Central Mesencephalic Reticular Formation and Cervical Spinal Cord in the Cat and Macaque

Abstract: A gaze-related region in the caudal midbrain tegementum, termed the central mesencephalic reticular formation (cMRF), has been designated on electrophysiological grounds in monkeys. In macaques, the cMRF correlates with an area in which reticulotectal neurons overlap with tectoreticular terminals. We examined whether a region with the same anatomical characteristics exists in cats by injecting biotinylated dextran amine into their superior colliculi. These injections showed that a cat cMRF is present. Not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 60 publications
6
32
1
Order By: Relevance
“…Reticulospinal neurons projecting to cervical spinal cord and medullary reticuloreticular cMRF neurons projecting to the rostral medullary reticular formation occupy just the medial portion of the cMRF (Fig. 11A) [primate: (Castiglioni et al 1978; Perkins et al 2014; Robinson et al 1994; Warren et al 2008); cat: (Perkins et al 2014; Satoda et al 2002)]. As we have shown here, the presence of a narrow band of cells labeled from oculomotor injections, reveals an unreported subdivision with direct projections to the SOA and III (Fig.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Reticulospinal neurons projecting to cervical spinal cord and medullary reticuloreticular cMRF neurons projecting to the rostral medullary reticular formation occupy just the medial portion of the cMRF (Fig. 11A) [primate: (Castiglioni et al 1978; Perkins et al 2014; Robinson et al 1994; Warren et al 2008); cat: (Perkins et al 2014; Satoda et al 2002)]. As we have shown here, the presence of a narrow band of cells labeled from oculomotor injections, reveals an unreported subdivision with direct projections to the SOA and III (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…Further examination of the feedback pathway revealed that the ipsilateral reticulotectal projection was GABAergic, and the contralateral projection contained both GABAergic and non-GABAergic elements (Wang et al 2010). The role of the cMRF in controlling head movements also was supported by anatomical studies in cats and monkeys (Perkins et al 2009; Warren et al 2008; Zhou et al 2008). Specifically, cMRF projections to the cervical cord and to reticulospinal neurons in the medullary reticular formation were demonstrated.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…The red nucleus sends a major tract to the contralateral spinal cord in mammalian and non-mammalian vertebrates (Kuypers et al 1962;Poirier and Bouvier 1966;Warner and Watson 1972;Miller and Strominger 1973;Castiglioni et al 1978;Crutcher et al 1978;Wild et al 1979;Smeets and Timerick 1981;Huisman et al 1982;Carlton et al 1985;Okado and Oppenheim 1985;Prasada Rao et al 1987;Nudo and Masterton 1988;Masino and Knudsen 1992;New et al 1998;Cruce et al 1999;Carretta et al 2001;Satoda et al 2002;Tsukamoto et al 2003;Chiocchetti et al 2006;VanderHorst and Ulfhake 2006;Stockx et al 2007;Warren et al 2008). As with the corticospinal projection (see above), the exception is the hedgehog, in which the ipsilateral projection is larger than the contralateral (Kunzle 1992).…”
Section: Red Nucleusmentioning
confidence: 99%
“…One possibility is that stimulation recruited fibers that traverse through the PPRF region and relay projections to the neck motoneurons (e.g., May and Porter 1992;Warren et al 2008). Another candidate is a subset of reticulospinal neurons that reside in the PPRF region Robinson et al 1994).…”
Section: Effectors Controlled By Pprf Neuronsmentioning
confidence: 99%